Effect of flow management on ultrasonic melt processing in a launder upon DC casting - Subroto, Tungky; Eskin, Dmitry G.; Beckwith, Christopher; Roberts, Dan; Tzanakis, Iakovos; Pericleous, Koulis A. (Light metals 2022)
A promising strategy for upscaling ultrasonic melt treatment (UST) during direct-chill (DC) casting is through a strategically placed flow management system in the launder. This aims at improving the melt residence time and acoustic pressure distribution, which ultimately optimizes the treatment efficiency. This work focuses on observing the effect of partitions and UST on the resultant grain refinement upon DC casting of an AA6XXX aluminum alloy with Zr additions. Billets 152 mm in diameter were cast in a pilot-scale DC casting facility: cases with and without partitions and with and without UST were compared. The effect of partitions on the UST efficiency was quantified through macro- and microstructure observations and supported with acoustic pressure measurements. The positive impact of partitions on the grain refinement upon UST is demonstrated.